Chiral mirror-baryon-meson model and nuclear matter beyond mean-field approximation - Weyrich, Johannes; Strodthoff, Nils; Smekal, Lorenz von (Physical review. C, Nuclear physics, 2015)
We consider a chiral baryon-meson model for nucleons and their parity partners in mirror assignment interacting with pions and sigma and omega mesons to describe the liquid-gas transition of nuclear matter together with chiral symmetry restoration in the high density phase. Within the mean-field approximation the model is known to provide a phenomenologically successful description of the nuclear-matter transition. Here, we go beyond this approximation and include mesonic fluctuations by means of the functional renormalization group. While these fluctuations do not lead to major qualitative changes in the phase diagram of the model, beyond the mean-field approximation, one is no longer free to adjust the parameters so as to reproduce the binding energy per nucleon, the nuclear saturation density, and the nucleon sigma term all at the same time. However, the prediction of a clear first-order chiral transition at low temperatures inside the high baryon-density phase appears to be robust.
Gesehen am 01.07.2020